Hello,
Answer A
s(x)=3x-7
s(2t-4)=3*(2t-4)-7=6t-12-7=6t-19
Answer:
C
Step-by-step explanation:
So we have the product of:
![(-6x^3y^5)\cdot(-4y^2)](https://tex.z-dn.net/?f=%28-6x%5E3y%5E5%29%5Ccdot%28-4y%5E2%29)
Multiply. Combine like terms:
![=(-6\cdot -4)(x^3)(y^5\cdot y^2)](https://tex.z-dn.net/?f=%3D%28-6%5Ccdot%20-4%29%28x%5E3%29%28y%5E5%5Ccdot%20y%5E2%29)
The first term is 24.
The second term stays as it is.
The third term will equate to y^7. Recall how to multiply exponents. The base stays constant and you add the exponents. Thus:
![=24x^3y^7](https://tex.z-dn.net/?f=%3D24x%5E3y%5E7)
Our answer is C.
And we're done!
Answer:
The answer is 21.5625
Step-by-step explanation:
The reason is because it first says 5 miles=8 km so that helps us right there.We divide 34.5 by 8 which will give us 4.3125.Then you have to multiply that by 5 which will give us 21.5625.
Answer:
153.86
Step-by-step explanation:
3.14(7)^2
3.14 × (7 × 7)
3.14 × 49
153.86
Answer:
No
Step-by-step explanation:
According to the property of the triangle ,
sum of any two sides should we greater then third side of the triangle.
Here, Measurement of three sides are given as 3,3,5 .
So, sum of the measurement of first two sides is 6.
And third side equals 10.
Clearly 6 is less than 10. So . it violates the property sum of any two sides should we greater then third side of the triangle.
Thus , Sides of a triangle can't be 3,3,10.